CCNP security firewall 642-618 official cert guide - Hucaby, Dave.; Garneau, Dave.; Sequeira, Anthony; Cisco Systems, Inc. (Indianapolis, Ind. : Cisco Press, 2012)
Presents an organized test preparation routine through the use of proven series elements and techniques.
Includes bibliographical references and index.
oif 23/06/15
Loan
Keywords: Electronic data processing personnel -- Certification -- Study guides; Computer networks -- Security measures -- Examinations -- Study guides; Firewalls (Computer security) -- Examinations -- Study guides